Forced Degradation Study of Sofosbuvir: Identification of Degradation Products by LC-ESI-MS - Agarwal, Babita; Jagdale, Sachin; Gandhi, Santosh (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: In order to establish stability indicating techniques to comprehend the degradation behavior of drug under stress environments and to establish degradation pathway for drug substance, forced degradation is a potential tool employed more frequently in pharmaceutical developments. The sole need of present research was to establish stability and forced degradation pathway profiling of sofosbuvir. Methods: The stability of sofosbuvir has been validated by RP-HPLC method, where mixture of Methanol: Water with 0.1 % formic acid (50:50 % v/v) was used as mobile phase at 1.0 mL/min in gradient method. Different stress conditions were employed as per ICH guidelines. Results: Total three degradation products (DPs) were observed. In acidic and alkaline conditions hydrolysis product was found to be DP I at a Rt 4.2, with m/z 488 and DP II at a Rt 3.6, with m/z, 393.3 respectively. In oxidative state with H2O2 as oxidizing agent, DP III at RT 3.2, with m/z at 393. Discussion and Conclusion: Sofosbuvir showed degradation in acidic, basic and oxidative medium. No degradation was observed in thermal, UV light and neutral conditions. 23% degradation was seen in acidic medium and DP I with m/z value of 487 could be due to removal of C(CH3)2 from methoxy end of molecular structure. 50% degradation was observed in alkaline conditions and DP II with m/z value of 488 was seen in ESI source in MS. Oxidative degraded products could be formed due to formation of amine oxide which may be formed from tertiary amines by hydrogen peroxide.
Keywords: Sofosbuvir; Degradation; HPLC; LC-ESI-MS; Pathway